Global safety monitoring of COVID-19 vaccines: how pharmacovigilance rose to the challenge. (August 2022) - Rudolph, Annette; Mitchell, Joseph; Barrett, Jim; Sköld, Helena; Taavola, Henric; Erlanson, Nils; Melgarejo-González, Carlos; Yue, Qun-Ying
Pharmacovigilance (PV) came suddenly into the spotlight when several new vaccines, developed as a response to the COVID-19 pandemic, received emergency authorisation and were rolled out on a large scale in late 2020. The vaccines underwent stringent clinical trials and evaluation from regulatory authorities, but with the use of novel technology and an anticipated rapid and vast deployment of the vaccines, the importance of a well-functioning international post marketing safety surveillance system was stressed. International PV stakeholders were faced with several challenges due to the extent of the global vaccination campaign. The unprecedented volume of reports of suspected adverse events following immunization has led to the development and use of new tools. Furthermore, the collaboration between various PV stakeholders was encouraged and strengthened. PV rose to the challenges posed by the currently ongoing global COVID-19 vaccination campaign and successful adaptations were made in a short period of time. However, the pandemic has not ended yet, the vaccination campaign is far from being completed, and further challenges are anticipated. Advances made during the pandemic will be important to strengthen PV in future and ensure to advance medicines' safety together. Plain Language Summary: Global safety monitoring of the COVID-19 vaccines: challenges, preparations, and outlooks Pharmacovigilance (PV) is the umbrella term for all sciences and activities relating to the detection, assessment, understanding, and prevention of adverse effects relating to medicines or vaccines. PV came into the spotlight when several new vaccines were authorised and rolled out as a response to the COVID-19 pandemic. The anticipated extent of the global vaccine rollout stressed the importance of a well-functioning safety surveillance system and international collaborations between patients, health care workers, vaccine producers, regulatory authorities, and PV centres. The identification and communication of potential safety concerns showed that adaptations to PV processes made in a short period of time as well as international collaborations were successful. However, it is important to learn from experiences made so far and to make sure the positive advances are maintained in the future to advance medicines' safety together.